PENINGKATAN EFISIENSI DAN PRODUKTIVITAS OPERASIONAL PADA NELAYAN TRADISIONAL MELALUI PENGAPLIKASIAN KONSEP LEAN AND GREEN SUPPLY CHAIN MANAGEMENT - Citra Indah Asmarawati; Sadiq Ardo Wibowo (Universitas Putera Batam, 2026)
The traditional fisheries sector in Indonesia still faces various challenges in terms of operational efficiency and productivity, driving the need for innovative solutions to improve the performance of this sector. This study aims to analyze and improve the operational performance of traditional fishermen through the application of the Lean and Green Supply Chain Management (LGSCM) concept, using a mixed-method approach that combines quantitative and qualitative analysis. Data were collected through direct observation, in-depth interviews with 50 traditional fishermen, and measurement of operational parameters over a 6-month period. The results of the study identified significant waste in the traditional fisheries supply chain, including an average waiting time of 4.2 hours per trip, excess fuel consumption of up to 12 liters per trip, and a loss of 8.5 kg of catch per trip due to improper handling. The implementation of LGSCM which includes standardization of work processes, optimization of shipping routes, improvement of fish storage systems, and the use of appropriate technology has resulted in significant improvements. After the application of this concept, there was a reduction in waiting time to 2.3 hours per trip, a decrease in fuel consumption to 8.4 liters per trip, and an increase in marketable catch to 32.5 kg per trip. The conclusion of the study shows that the application of LGSCM has not only succeeded in increasing the efficiency and productivity of traditional fishermen's operations, but also contributed to reducing the environmental impact of fishing activities. This study recommends the need for ongoing training programs, increased infrastructure support, and the development of policies that support the adoption of LGSCM practices in the traditional fisheries sector to ensure the sustainability of its implementation and benefits in the long term.